Prevalência de perdas urinárias em uma amostra de mulheres de Botucatu - Vianna, Luana Schneider [UNESP] (2013)
The goal of this study was to determine the prevalence of urinary incontinence (UI), presence or absence of bother with the UI and to observe the most common at the moment of the urinary loss from the city of Botucatu. This is a transversal epidemiological study made in two hospitals with maternity in operation in the city of Botucatu, Brazil. Women were interviewed during hospitalization for childbirth, at the time of postpartum when they responded the structured survey. Results: It was interviewed 299 women, of these 49 (16.4%) were incontinent and among the incontinent 27 (55.1%) had mixed urinary incontinence (MUI) and 23 (46.9%) reported discomfort related to UI. Among the most common activities during the loss of urine were found sneeze, cough, laugh, and when they were strong urge to urinate. These findings highlight the importance of research on the prevalence of UI as well as approach and care for women with this symptom